Laporan Kasus : Upaya Pendekatan Kedokteran Keluarga Melalui Kunjungan Rumah pada Wanita 60 Tahun dengan Hipertensi dan Hiperkolesterolemia di Kabupaten Pamekasan - Ramona Frisca Ariansyah; Dzulfira Arifah; Anang Triadi; Nur Khamidah (Pusat riset dan Inovasi Nasional, 2026)
Hypertension and hypercholesterolemia are closely related non-communicable diseases and major risk factors for cardiovascular disease, particularly in older adults. These conditions are influenced by medical, behavioral, family, and environmental factors, requiring a holistic family medicine approach through home visits. This study aimed to describe the clinical condition, family function, and environmental factors of a 60-year-old female patient with hypertension and hypercholesterolemia using the APGAR and SCREEM approaches. This study employed a qualitative descriptive design in the form of a case report involving Mrs. S (60 years old) in Lebbek Village, Pamekasan Regency. Data were collected through anamnesis, physical examination, total cholesterol measurement using a GCU meter, environmental observation, and assessment of family function and environmental factors. The results showed blood pressure values of 161/96 mmHg and 160/96 mmHg on repeated measurement, with a total cholesterol level of 154 mg/dL. The patient had a high-salt and high-fat diet with low physical activity. APGAR assessment indicated poor family function with a total score of 4, particularly in the partnership and resolve domains, while the growth domain was categorized as accepting. SCREEM analysis identified education as the main barrier. In conclusion, management of this condition requires family-based interventions focusing on improving family cooperation and health education tailored to the patient’s literacy level.